Balloon-expanding stent and delivery system for transcatheter aortic valve implantation: An animal study. Issue 2 (June 2015) - Chen, Xiang; Wang, Fei-Yu; Chu, Guo-Jun; Zhu, Yu-Feng; Tan, Hong-Wen; Zhao, Xian-Xian; Qin, Yong-Wen; Ge, Jun-Bo
Abstract: Objective: To evaluate the feasibility and satefy of transcatheter aortic valve implantation in animals by using a new balloon-expanding valved stent. Methods: The balloon-expandable stent is made from cobalt-based alloy material and designed with a tubular, slotted structure. Fresh bovine pericardium was treated, sutured and fixed on the balloon-expandable stent. Ten healthy sheep (five males and five females), weighing an average of (25.16 ± 1.83) kg, were selected to undergo transcatheter implantation of the valve stents. The function of the valve stent was evaluated by angiography, echocardiography, and histology six months after the procedure. Results: Of the ten experimental sheep, two sheep died during the operation because the higher position of the artificial valve affected the opening of the coronary artery. We successfully implanted the aortic valve stent in other eight sheep; however, one sheep died of heart failure two weeks after the operation due to the lower position of the valve stent. The valve stents were implanted in the desired position in seven sheep. Ascending aortic angiographic and autoptic findings immediately after the operation confirmed the satisfactory location and function of the valved stent. Echocardiography, angiography, and histology at six postoperative months confirmed the satisfactory location and function of the valve stent. Conclusion: We successfully implanted our new valve stent as a replacement of native aortic valve via the transcatheter route with satisfactory outcome.